Gonococcal Conjunctivitis Despite Successful Treatment of Male Urethritis Syndrome. Issue 2 (February 2016) - Peters, Remco P.H.; Verweij, Stephan P.; McIntyre, James A.; Schaftenaar, Erik
Abstract : Abstract: We report a case of progressive, cephalosporin-susceptible, Neisseria gonorrhoeae conjunctivitis despite successful treatment of male urethritis syndrome. We hypothesize that conjunctival infection progressed due to insufficient penetration of cefixime and azithromycin and point out that extragenital infection and male urethritis may not be cured simultaneously in settings where the syndromic approach is used.